Health service utilization and experiences of stigma amongst people who inject drugs in Melbourne, Australia. Issue 12 (17th September 2021) - Djordjevic, Filip; Ryan, Kathleen; Gunn, Jack; Brener, Loren; O'Keefe, Daniel; Draper, Bridget; Schroeder, Sophia; Gold, Judy; Treloar, Carla; Broady, Tim; Dietze, Paul; Hellard, Margaret; et al.
Abstract: Whilst the testing and treatment of people who inject drugs (PWID) in Australia is a priority for local hepatitis C (HCV) elimination efforts, perceived stigma related to injecting drug use (IDU) has been identified as a major barrier for PWID engaging in health services. We used data from the EC Experience cohort study to explore associations between IDU‐related perceived stigma and the number of different health services accessed by PWID in Melbourne, Australia. Data from the baseline questionnaire were used. Primary outcome was self‐reported experience of stigma due to IDU (never, rarely, sometimes, often, always) in the previous 12 months. An ordinal logistic regression model assessed the association between stigma experienced and the number of different health services used (1–2, 3–4, 5–6, 7–10 different services) adjusted for recent IDU and key socio‐demographics. Between September 2018 and February 2020, 281 participants were recruited from four health services. Sixty‐nine per cent were male, median age was 42, 83% reported past‐month IDU, 34% had never tested/tested >12 months, 8% tested negative <12 months, 43% were HCV‐positive but not treated and 16% had been treated. Those accessing 5–6 services had 2.2 times greater odds of experiencing stigma (95% CI 0.86–6.65) compared with those using <5 services and those reporting 7–10 services had 2.43 times greater odds of experiencing stigma (95% CI 0.85–6.92) compared with those accessing <7 services. In conclusion, experiences of stigma may not necessarily be a barrier for PWID to access health services, but high rates of health service use may further expose, exacerbate or exaggerate stigma amongst PWID. Further examination of how stigma may be in/directly impact on hepatitis C treatment uptake is important and place‐based interventions aimed at reducing stigma experienced by PWID may be needed.